2013
DOI: 10.1364/oe.21.004958
|View full text |Cite
|
Sign up to set email alerts
|

Improved InGaN/GaN light-emitting diodes with a p-GaN/n-GaN/p-GaN/n-GaN/p-GaN current-spreading layer

Abstract: This work reports both experimental and theoretical studies on the InGaN/GaN light-emitting diodes (LEDs) with optical output power and external quantum efficiency (EQE) levels substantially enhanced by incorporating p-GaN/n-GaN/p-GaN/n-GaN/p-GaN (PNPNP-GaN) current spreading layers in p-GaN. Each thin n-GaN layer sandwiched in the PNPNP-GaN structure is completely depleted due to the built-in electric field in the PNPNP-GaN junctions, and the ionized donors in these n-GaN layers serve as the hole spreaders. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
45
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 40 publications
0
45
0
Order By: Relevance
“…Other simulation parameters such as the Shockley-Read-Hall recombination lifetime of 43 ns, Auger recombination coefficient of 1 Â 10 À30 cm 6 /s, and the band offset ratio of 70/30 for the InGaN/GaN MQW can also be found in our previously published works. 13,[18][19][20][21][22] The electric field profiles under the equilibrium have been shown in Fig. 5(a).…”
Section: -mentioning
confidence: 99%
“…Other simulation parameters such as the Shockley-Read-Hall recombination lifetime of 43 ns, Auger recombination coefficient of 1 Â 10 À30 cm 6 /s, and the band offset ratio of 70/30 for the InGaN/GaN MQW can also be found in our previously published works. 13,[18][19][20][21][22] The electric field profiles under the equilibrium have been shown in Fig. 5(a).…”
Section: -mentioning
confidence: 99%
“…InGaN/GaN multiple quantum well (MQW) lightemitting diodes (LEDs) have made significant progress in the past three decades. [1][2][3] The device performance is, however, still limited by Auger recombination, 4,5 charge separation, 6-9 current crowding, [10][11][12] insufficient hole injection, 9,[13][14][15][16][17][18] and electron overflow from the MQW active region. [19][20][21][22] In order to address these issues, a staggered quantum well architecture and also InGaN/GaN MQWs with Si-step-doped quantum barriers have been proposed to screen the quantum confined Stark effect (QCSE) and increase the spatial overlap of electron-hole wave functions, [7][8][9] while an improved current spreading can be obtained either by making the p-type layer more resistive or the p-contact layer more conductive.…”
mentioning
confidence: 99%
“…[19][20][21][22] In order to address these issues, a staggered quantum well architecture and also InGaN/GaN MQWs with Si-step-doped quantum barriers have been proposed to screen the quantum confined Stark effect (QCSE) and increase the spatial overlap of electron-hole wave functions, [7][8][9] while an improved current spreading can be obtained either by making the p-type layer more resistive or the p-contact layer more conductive. 10,11 Additionally, an improved crystal quality is also essential for improving the device efficiency. 23 Furthermore, it has been reported that an enhanced hole injection efficiency can be obtained through utilizing a thinner quantum barrier 17,18 or a thinner quantum well.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 To this end, tremendous efforts have been devoted to improve the LED performance through addressing various issues related to material quality, structure optimization, and device design and fabrication. [3][4][5][6][7][8][9][10][11][12] Among these issues, to date a low p-type doping efficiency remains as a limiting factor, which adversely affects the LED performance. In typical p-type GaN, the resulting hole concentration is low because only $1% of Mg dopants are ionized at room temperature.…”
mentioning
confidence: 99%